Black rot of squash (Cucurbita moschata) caused by Stagonosporopsis cucurbitacearum reported in Italy - Moumni, Marwa; Mancini, Valeria; Allagui, Mohamed Bechir; Murolo, Sergio; Romanazzi, Gianfranco (Phytopathologia Mediterranea, 2019)
Stagonosporopsis cucurbitacearum (syn. Didymella bryoniae) can affect cucurbits through induction of black rot. This pathogen produces irregular white spots covered with pycnidia on infected cucurbit fruit. Twenty squash fruit (cv. Butternut) with black rot symptoms were collected in Italy from two locations: Osimo (AN) and Montacuto (AN), in the Marche region. Several fungal colonies were isolated from these fruit, the morphological features of which corresponded to S. cucurbitacearum. This identification was confirmed using multiplexing of three microsatellite markers and by sequence analysis using internal transcribed spacers. The sequence identity for the internal transcribed spacer regions was greater than 98% compared with sequences of S. cucurbitacearum in the NCBI database. This is the first report of S. cucurbitacea-rum on Cucurbita moschata fruit with black rot symptoms in Italy.